A flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet and preparation method thereof

By adopting a "sandwich structure" composite material with thermally conductive polyimide-based graphite film and perforated modified natural graphite film, and introducing modified graphene oxide and insulating thermal coating, the existing heat dissipation graphite sheets are solved, and a composite heat dissipation graphite sheet with high thermal conductivity, flexibility and electrical safety is achieved.

CN118991160BActive Publication Date: 2025-04-04DONGGUAN HONGYI THERMAL CONDUCTMTY MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411096666.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-04-04
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

Due to poor flexibility and thermal conductivity, existing heat dissipation graphite sheets cannot meet the demand for high-end market for bendable, highly thermally conductive, and ultra-tough composite heat dissipation materials.

Method used

The "sandwich structure" composite material consisting of a thermally conductive polyimide-based graphite film, a perforated modified natural graphite film, a thermally conductive polyimide-based graphite film and a thermally conductive insulating layer is used to improve the thermal conductivity, flexibility and electrical safety of the material through the introduction of modified graphene oxide and insulating thermal coatings.

Benefits of technology

The composite heat dissipation graphite sheet has achieved excellent flexibility, flexibility, high thermal conductivity and electrical safety, and is suitable for electronic equipment, automobiles, aerospace and other fields, especially in scenarios where efficient heat dissipation and maintaining the flexibility of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004988126710000101
    Figure BDA0004988126710000101
  • Figure HDA0004988126720000011
    Figure HDA0004988126720000011
Patent Text Reader

Abstract

The present application relates to the technical field of heat dissipation materials, and in particular to a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet and a preparation method thereof. A flexible high-thermal-conductivity and ultra-tough composite heat-dissipating graphite sheet comprises, from bottom to top, a thermally conductive polyimide-based graphite film, a perforated modified natural graphite film, a thermally conductive polyimide-based graphite film and a thermally conductive insulating layer, wherein the thermally conductive insulating layer is formed by coating an insulating thermally conductive coating, and the thermally conductive polyimide-based graphite film is prepared by graphitizing a thermally conductive polyimide composite film; the thickness of the thermally conductive polyimide-based graphite film is 50-100 μm, the thickness of the perforated modified natural graphite film is 100-200 μm, and the thickness of the thermally conductive insulating layer is 5-10 μm, wherein the thermally conductive polyimide composite film, in parts by mass, is prepared from raw materials comprising: 102.165 parts of 4,4′-diaminodiphenyl ether, 54.07 parts of p-phenylenediamine, 2170 parts of dimethylacetamide, 227.2 parts of pyromellitic anhydride, and 5-8 parts of modified graphene oxide. The high thermal conductivity and ultra-tough composite heat dissipation graphite sheet of the present application has the characteristics of excellent flexibility, bendability, high thermal conductivity and electrical safety, and is widely used in electronic equipment, automobiles, aerospace and other fields, especially in scenarios that require efficient heat dissipation and maintaining equipment flexibility, such as flexible display screens, wearable devices, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of heat dissipation materials, and in particular to a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet and a preparation method thereof. Background Art

[0002] Nowadays, with the development of electronic equipment integration, miniaturization and high performance, flexible polymer-based composite materials with anisotropic thermal conductivity and electrical conductivity have attracted widespread attention. In order to prevent heat accumulation from affecting the normal operation of electronic equipment, the composite material used as a heat sink should quickly dissipate waste heat in the in-plane direction to avoid excessive temperature of electronic equipment affecting its operating performance and other safety hazards. At present, the mainstream chip heat dissipation method is graphite heat dissipation. Graphite heat sinks are applied to the chip surface in the form of thin films. The central temperature of the chip heat is distributed to a large area to uniformly dissipate heat. However, the processing (high temperature and high pressure shaping) and applicability (graphite flakes are brittle) of heat dissipation graphite sheets are relatively poor, which is not conducive to its practical application. However, graphite has a unique grain orientation. This structure determines the anisotropy of graphite, making the thermal conductivity in the direction parallel to the graphite layer as high as 1500W / (m·K), while the highest thermal conductivity in the direction perpendicular to the graphite layer is only 10-20W / (m·K). When the graphite thermal conductive sheet is in use, heat is first transferred in a direction perpendicular to the graphite layer and then in a direction parallel to the graphite layer. However, the thermal conductivity in the direction perpendicular to the graphite layer is low, which greatly limits the thermal conductivity of the graphite sheet.

[0003] Currently, in the fields of electronic equipment, automobiles, aerospace, etc., especially in scenarios that require efficient heat dissipation and maintaining equipment flexibility, such as flexible display screens and wearable devices, flexible, high-thermal-conductivity, ultra-tough composite heat dissipation graphite sheets are needed. The existing heat dissipation graphite sheets cannot meet the needs of the high-end market well due to their poor flexibility and thermal conductivity. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present application provides a flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet and a preparation method thereof. The flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet of the present application has excellent flexibility, bendability, high thermal conductivity and electrical safety, and is widely used in electronic equipment, automobiles, aerospace and other fields, especially in scenarios that require efficient heat dissipation and maintaining device flexibility, such as flexible display screens, wearable devices, etc.

[0005] In a first aspect, the present application provides a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, which adopts the following technical solution:

[0006] A flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, the flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises, from bottom to top, a thermally conductive polyimide-based graphite film, a perforated modified natural graphite film, a thermally conductive polyimide-based graphite film and a thermally conductive insulating layer, the thermally conductive insulating layer is formed by coating an insulating thermally conductive coating, the thermally conductive polyimide-based graphite film is prepared by graphitizing a thermally conductive polyimide composite film; the thickness of the thermally conductive polyimide-based graphite film is 5 0-100μm, the thickness of the perforated modified natural graphite film is 100-200μm, the thickness of the thermal conductive insulating layer is 5-10μm, wherein the thermal conductive polyimide composite film, calculated by mass, is prepared from raw materials including: 102.165 parts of 4,4′-diaminodiphenyl ether, 54.07 parts of p-phenylenediamine, 2170 parts of dimethylacetamide, 227.2 parts of pyromellitic anhydride, and 5-8 parts of modified graphene oxide.

[0007] By adopting the above technical scheme, the flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet of the present application achieves excellent flexibility, bendability, high thermal conductivity and electrical safety through the synergistic effect of each layer of materials. Thermally conductive polyimide-based graphite film: As the main component of the composite heat dissipation graphite sheet, it gives it excellent flexibility and bendability. At the same time, the vertical thermal conductivity and flexibility of the thermally conductive polyimide-based graphite film are improved by the introduction of modified graphene oxide. Perforated modified natural graphite film: By calendering and perforating modified natural flake graphite, a perforated modified natural graphite film with burrs on both sides is obtained. This structure significantly improves the thermal conductivity of the composite heat dissipation graphite sheet. Thermally conductive insulation layer: It is formed by coating with an insulating thermal conductive coating and has good insulation and thermal conductivity. The obtained composite heat dissipation graphite sheet has good insulation and heat dissipation properties, reducing the possibility of leakage. The functions and synergistic effects of each component in the thermally conductive polyimide composite film of the present application are as follows: 4,4′-diaminodiphenyl ether: As one of the monomers of polyimide, it provides a rigid benzene ring structure, increases the regularity and rigidity of the polymer chain, and helps to improve the thermal stability and mechanical properties of the polyimide. Paraphenylenediamine: As another monomer of polyimide, it forms the backbone of the polymer chain together with 4,4′-diaminodiphenyl ether, provides an additional aromatic ring structure, and enhances the thermal stability and chemical stability of the polymer. Dimethylacetamide: As a solvent, it is used to dissolve other components to ensure that the reaction proceeds evenly, and also serves as a medium in the polymerization process. Isomellitic dianhydride: As another monomer of polyimide, it undergoes a condensation reaction with the diamino monomer to form polyimide. Its symmetrical structure helps to improve the crystallinity and regularity of the polymer. Modified graphene oxide: By introducing active functional groups such as carboxyl, hydroxyl, and epoxy, the interaction with the polyimide matrix is ​​increased, the graphite lattice structure is improved, the heat transfer capacity in the vertical direction is improved, and the flexibility and thermal conductivity of the composite film are enhanced. In summary, the flexible, highly thermally conductive, ultra-tough composite heat dissipation graphite sheet of the present application achieves excellent flexibility, bendability, high thermal conductivity, and electrical safety through the synergistic effect of each layer of material. It has broad application prospects in the fields of electronic equipment, automobiles, aerospace, etc., especially in scenarios that require efficient heat dissipation and maintaining equipment flexibility, such as flexible displays, wearable devices, etc.

[0008] Preferably, the method for preparing the modified graphene oxide comprises the following steps:

[0009] S21, taking 100 parts of graphene oxide by mass and drying them in a vacuum drying oven at 100° C. for 12 h;

[0010] S22, according to the mass fractions, 95 parts of ethanol and 5 parts of deionized water were mixed, the pH was adjusted to 4 with acetic acid, and then 1.2 parts of 3-[3-carboxyallylamide]propyltriethoxysilane were added dropwise and ultrasonically stirred for 1-2 hours to obtain a mixed solution;

[0011] S23, adding 20 parts of dried graphene oxide to the mixed solution, heating the mixture to 62°C, stirring at 200 rpm, reacting for 4-5 hours, filtering, washing with anhydrous ethanol 3 times, and vacuum drying at 100°C for 24 hours to obtain modified graphene oxide.

[0012] By adopting the above technical scheme, the prepared modified graphene oxide plays multiple roles in the thermally conductive polyimide composite film, including: improving interface interaction: the active functional groups such as carboxyl, hydroxyl, and epoxy carried by the modified graphene oxide can establish molecular interactions between the layers of the thermally conductive polyimide-based graphite film. This enhanced interface interaction is conducive to improving the overall mechanical properties and thermal stability of the material, while improving the thermal conduction efficiency between the layers. Optimizing the graphite lattice structure: By introducing modified graphene oxide, the heat transfer restriction in the vertical direction can be improved, thereby significantly improving the vertical thermal conductivity of the thermally conductive polyimide-based graphite film. This is because modified graphene oxide helps to form a more continuous and orderly heat conduction path, reduce thermal resistance, and improve the thermal conductivity of the material. Enhanced flexibility and bendability: The introduction of modified graphene oxide not only improves the thermal conductivity, but also increases the flexibility and bendability of the composite material. This is particularly important for the preparation of high thermal conductivity and high flexibility heat dissipation materials that can be used in flexible display screens, wearable devices and other fields. In short, modified graphene oxide plays a key role in the preparation of high thermal conductivity and ultra-tough composite heat dissipation graphite sheets. It not only improves the thermal conductivity of the material, but also enhances its mechanical properties and electrical safety, making it more suitable for the stringent requirements of high-performance heat dissipation materials in modern electronic equipment and other fields.

[0013] Preferably, the method for preparing the perforated modified natural graphite film is to perform calendering and perforation treatment on modified natural flake graphite to obtain a perforated modified natural graphite film having burrs on both sides.

[0014] Preferably, the modification method of the modified natural flake graphite is: 30g of natural flake graphite is placed in a reactor filled with 3L of pure water and ultrasonically treated for 1-2h, and under the action of ultrasonic cavitation, enough defect sites are formed on the surface, and then 150g of ferrous sulfate is added and stirred evenly, and then the temperature is raised to 85°C, and then 5L of hydrogen peroxide with a mass concentration of 30% is dripped into the reactor, reacted for 24h and cooled to room temperature, and the natural flake graphite is washed with pure water 3 times, and then the modified natural flake graphite is dried at 60°C for 4h to obtain modified natural flake graphite.

[0015] By adopting the above technical solution, the natural flake graphite is modified by the Fenton reaction, so that a large number of defects and oxygen-containing functional groups are formed on the surface of the natural flake graphite. 3+ The OH adsorbed on the carbon fiber surface and free in the surrounding - It is converted into iron oxyhydroxide, and finally a protruding iron oxyhydroxide structure is formed on the surface of natural flake graphite, which is reduced to iron by carbon during the graphitization process to form a three-dimensional network structure, which significantly improves the compatibility and bonding strength with the perforated modified natural graphite film and the thermal conductivity channel, thereby improving the heat dissipation effect.

[0016] Preferably, the method for preparing the thermally conductive polyimide composite film comprises the following steps:

[0017] S51. According to the mass fractions, 102.165 parts of 4,4′-diaminodiphenyl ether and 54.07 parts of p-phenylenediamine were added to the reactor at room temperature and in a nitrogen atmosphere, and then 2170 parts of dimethylacetamide were added. After 4,4′-diaminodiphenyl ether and p-phenylenediamine were completely dissolved, the solution temperature was lowered to 10° C., 227.2 parts of pyromellitic dianhydride were added to the solution, and the mixture was stirred for 24 hours in an ice-water bath to obtain a yellow viscous polyamic acid solution.

[0018] S52. Add 5-8 parts of modified graphene oxide to the polyamic acid solution, stir mechanically for 1 hour under a nitrogen atmosphere to make the two mixed evenly, perform vacuum degassing for 2 hours, then coat the film on a clean and dry glass plate, and place it in a blast oven according to a gradient curing process of 80℃ / 1h+150℃ / 1h+250℃ / 1h+350℃ / 1h to dehydrate the polyamic acid and complete imidization. After the film is cooled to room temperature, peel off the film in hot water, dry the water, and obtain a thermally conductive polyimide composite film.

[0019] By adopting the above technical solution, the number of active functional groups such as carboxyl, hydroxyl, and epoxy carried by the modified graphene oxide increases, which can establish molecular interactions between the layers of the thermally conductive polyimide-based graphite film, improve the graphite lattice structure, and restrict the heat transfer in the vertical direction. The vertical thermal conductivity of the thermally conductive polyimide-based is significantly improved. The introduction of modified graphene oxide improves the vertical thermal conductivity and flexibility of the thermally conductive polyimide-based graphite film. The thermally conductive polyimide-based graphite film gives the composite heat dissipation graphite sheet excellent flexibility and bendability, allowing it to be widely used in electronic equipment, automobiles, aerospace and other fields, especially in scenarios that require efficient heat dissipation and maintaining equipment flexibility, such as flexible displays, wearable devices, etc.

[0020] Preferably, the insulating thermal conductive coating comprises, by weight, 20-22 parts of insulating thermal conductive agent, 1-1.5 parts of ethylene-ethyl acrylate copolymer, and 30-35 parts of acetone.

[0021] Preferably, the method for preparing the insulating thermal conductive agent comprises the following steps:

[0022] S71, weighing 1 kg of mica with a particle size of 2 microns and 50 kg of xylene, placing them in ultrasonic vibration for 8 minutes to obtain a mixture A;

[0023] S72, weighing 36 kg of methylphenyldimethoxysilane and 1.2 kg of tetramethyldivinyldisiloxane, mixing them evenly, adding them together with mixture A into the reaction kettle, stirring evenly, and heating to 50° C. to obtain mixture B;

[0024] S73. Weigh 3 kg of 1.6% sodium hydroxide solution, add it dropwise to mixture B, stir evenly, heat to 72°C, hydrolyze for 2 hours, raise the temperature to 80°C, distill at normal pressure, react for 5 hours, raise the temperature to 92°C, and distill under reduced pressure for 1 hour to remove the solvent and small molecule products, then add anhydrous ethanol for rinsing, dry, and obtain an insulating thermal conductor.

[0025] By adopting the above technical scheme, an insulating thermal conductor is prepared by using methylphenyl silicone oil and mica, and then a thermally conductive insulating layer formed by coating an insulating thermally conductive coating prepared from the insulating thermal conductor has good insulating and thermally conductive properties, so that the composite heat dissipating graphite sheet made of the insulating thermally conductive layer can play a good role in heat dissipation and insulation, thereby reducing the possibility of leakage.

[0026] In a second aspect, the present application provides a method for preparing a flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, using the following technical solution:

[0027] As a general technical concept, the present application also provides a method for preparing the above-mentioned flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, comprising the following steps:

[0028] S81, placing a perforated modified natural graphite film in the middle, covering the upper and lower surfaces with a thermally conductive polyimide composite film, performing a first calendering in a "sandwich structure", and undergoing carbonization, graphitization and a second calendering treatment to obtain a heat dissipation graphite sheet A;

[0029] S82, mixing the poly-insulating thermal conductor, ethylene ethyl acrylate copolymer and acetone uniformly according to parts by mass to obtain an insulating thermal conductive coating;

[0030] S83, coating an insulating thermally conductive coating on one side of the heat dissipation graphite sheet A, heating and curing the sheet, and obtaining a bendable, highly thermally conductive, and ultra-tough composite heat dissipation graphite sheet.

[0031] Preferably, in step S81, the process conditions of carbonization are: carbonization at a temperature of 1300-1400°C for 1 hour under a nitrogen atmosphere; the process conditions of graphitization are: graphitization at a temperature of 2850-2890°C for 1 hour under a nitrogen atmosphere; the first calendering and the second calendering treatment are both performed by pressing for 15-20 seconds at a pressure of 150 MPa using a shell-type fast press.

[0032] Preferably, in step S83, the heating temperature is 90-105° C., and the curing time is 60-70 seconds.

[0033] In summary, the present application includes at least one of the following beneficial technical effects:

[0034] 1. Excellent flexibility and bendability: By using thermally conductive polyimide-based graphite film, the composite heat dissipation graphite sheet has good flexibility and bendability, and can be used in a bent or folded state. It is suitable for flexible displays, wearable devices and other scenarios where the flexibility of the device needs to be maintained.

[0035] 2. High thermal conductivity: The "sandwich structure" is adopted, and the thermal conductivity of the composite heat dissipation graphite sheet is significantly improved by introducing perforated modified natural graphite film and thermally conductive polyimide-based graphite film. This structural design can effectively disperse heat and improve the heat dissipation effect.

[0036] 3. Electrical safety: By setting up a thermal insulation layer, the electrical safety of the composite heat dissipation graphite sheet during use is ensured. The thermal insulation layer has good insulation and thermal conductivity, which can reduce the possibility of leakage and protect the safe operation of electronic equipment.

[0037] 4. Improve heat dissipation effect: After the modified natural flake graphite is calendered and perforated, a perforated modified natural graphite film with burrs on both sides is obtained. This structure increases the compatibility and bonding strength with the perforated modified natural graphite film and the heat conduction channel, further improving the heat dissipation effect.

[0038] 5. Improvement of graphite lattice structure: The introduction of modified graphene oxide can establish molecular interactions between the thermally conductive polyimide-based graphite film layers, improve the graphite lattice structure, and restrict the vertical heat transfer. The vertical thermal conductivity of the thermally conductive polyimide-based film is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments:

[0040] Figure 1 This is a schematic diagram of the structure of a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet prepared in Example 3 of the present application;

[0041] In the figure, 1 represents a thermally conductive polyimide-based graphite film; 2 represents a perforated modified natural graphite film; 3 represents a thermally conductive polyimide-based graphite film; and 4 represents a thermally conductive insulating layer. DETAILED DESCRIPTION

[0042] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0043] Preparation Example 1 Preparation of modified graphene oxide

[0044] The preparation method of modified graphene oxide comprises the following steps:

[0045] S21, taking 100 g of graphene oxide according to mass fraction and drying it in a vacuum drying oven at 100° C. for 12 h;

[0046] S22, according to the mass fractions, 95g of ethanol and 5g of deionized water were mixed, the pH was adjusted to 4 with acetic acid, and then 1.2g of 3-[3-carboxyallylamide]propyltriethoxysilane was added dropwise and ultrasonically stirred for 1-2h to obtain a mixed solution;

[0047] S23, adding 20 g of dried graphene oxide to the mixed solution, heating the mixture to 62° C., stirring at 200 rpm, reacting for 4.5 h, filtering, washing with anhydrous ethanol three times, and vacuum drying at 100° C. for 24 h to obtain modified graphene oxide.

[0048] Preparation Example 2 Preparation of modified natural flake graphite

[0049] The modification method of modified natural flake graphite is as follows: 30g of natural flake graphite is placed in a reactor filled with 3L of pure water and ultrasonically treated for 1.5h. Under the action of ultrasonic cavitation, enough defect sites are formed on the surface. Then 150g of ferrous sulfate is added and stirred evenly. The temperature is raised to 85°C, and then 5L of 30% mass concentration of hydrogen peroxide is dripped into the reactor. The reaction is carried out for 24h and cooled to room temperature. The natural flake graphite is washed with pure water 3 times, and then the modified natural flake graphite is dried at 60°C for 4h to obtain modified natural flake graphite.

[0050] Preparation Example 3 Preparation of Insulating Thermal Conductive Agent

[0051] The preparation method of the insulating thermal conductive agent comprises the following steps:

[0052] S71, weighing 1 kg of mica with a particle size of 2 microns and 50 kg of xylene, placing them in ultrasonic vibration for 8 minutes to obtain a mixture A;

[0053] S72, weighing 36 kg of methylphenyldimethoxysilane and 1.2 kg of tetramethyldivinyldisiloxane, mixing them evenly, adding them together with mixture A into the reaction kettle, stirring evenly, and heating to 50° C. to obtain mixture B;

[0054] S73. Weigh 3 kg of 1.6% sodium hydroxide solution, add it dropwise to mixture B, stir evenly, heat to 72°C, hydrolyze for 2 hours, raise the temperature to 80°C, distill at normal pressure, react for 5 hours, raise the temperature to 92°C, and distill under reduced pressure for 1 hour to remove the solvent and small molecule products, then add anhydrous ethanol for rinsing, dry, and obtain an insulating thermal conductor.

[0055] Example 1

[0056] A flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, the flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises, from bottom to top, a thermally conductive polyimide-based graphite film, a perforated modified natural graphite film, a thermally conductive polyimide-based graphite film and a thermally conductive insulating layer, the thermally conductive insulating layer is formed by coating an insulating thermally conductive coating, the thermally conductive polyimide-based graphite film is prepared by graphitizing a thermally conductive polyimide composite film, and the preparation method of the perforated modified natural graphite film is to perform calendering and perforation treatment on the modified natural flake graphite to obtain A perforated modified natural graphite film with burrs on both sides; the thickness of the thermally conductive polyimide-based graphite film is 50 μm, the thickness of the perforated modified natural graphite film is 200 μm, and the thickness of the thermally conductive insulating layer is 5 μm, wherein the thermally conductive polyimide composite film, by mass fraction, is prepared from raw materials including: 102.165 g of 4,4′-diaminodiphenyl ether, 54.07 g of p-phenylenediamine, 2170 g of dimethylacetamide, 227.2 g of pyromellitic anhydride, and 5 g of modified graphene oxide;

[0057] The method for preparing the thermally conductive polyimide composite film comprises the following steps:

[0058] S51. According to the mass fractions, 102.165 g of 4,4′-diaminodiphenyl ether and 54.07 g of p-phenylenediamine were added to the reactor at room temperature and in a nitrogen atmosphere, and then 2170 g of dimethylacetamide was added. After 4,4′-diaminodiphenyl ether and p-phenylenediamine were completely dissolved, the solution temperature was lowered to 10° C., 227.2 g of pyromellitic dianhydride was added to the solution, and the mixture was stirred for 24 h in an ice-water bath to obtain a yellow viscous polyamic acid solution.

[0059] S52, adding 5g of modified graphene oxide to the polyamic acid solution, mechanically stirring for 1h under a nitrogen atmosphere to mix the two evenly, vacuum degassing for 2h, and then coating on a clean and dry glass plate, and placing in a blast oven according to a gradient curing process of 80℃ / 1h+150℃ / 1h+250℃ / 1h+350℃ / 1h to dehydrate the polyamic acid to complete imidization, and after the film is cooled to room temperature, peel off the film in hot water, dry the water, and obtain a thermally conductive polyimide composite film;

[0060] The insulating thermal conductive coating is prepared from the following raw materials, calculated by weight: 20 g of insulating thermal conductive agent, 1 g of ethylene-ethyl acrylate copolymer, and 30 g of acetone.

[0061] The method for preparing the above-mentioned flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises the following steps:

[0062] S81, placing a perforated modified natural graphite film in the middle, covering the upper and lower surfaces with a thermally conductive polyimide composite film, performing the first calendering in a "sandwich structure", and undergoing carbonization, graphitization and a second calendering treatment to obtain a heat dissipation graphite sheet A; the process conditions for the carbonization are: carbonization at a temperature of 1300° C. for 1 h in a nitrogen atmosphere; the process conditions for the graphitization are: graphitization at a temperature of 2890° C. for 1 h in a nitrogen atmosphere; the first calendering and the second calendering treatments are both performed by using a shell-type fast press at a pressure of 150 MPa for 15 seconds;

[0063] S82, mixing the insulating thermal conductive agent, ethylene-ethyl acrylate copolymer and acetone uniformly according to the weight ratio to obtain an insulating thermal conductive coating;

[0064] S83, coating the insulating thermal conductive coating on one side of the heat dissipation graphite sheet A, heating and curing, the heating temperature is 90° C., the curing time is 70 seconds, and a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet is obtained.

[0065] Example 2

[0066] A flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, the flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises, from bottom to top, a thermally conductive polyimide-based graphite film, a perforated modified natural graphite film, a thermally conductive polyimide-based graphite film and a thermally conductive insulating layer, the thermally conductive insulating layer is formed by coating an insulating thermally conductive coating, the thermally conductive polyimide-based graphite film is prepared by graphitizing a thermally conductive polyimide composite film, and the preparation method of the perforated modified natural graphite film is to perform calendering and perforation treatment on the modified natural flake graphite to obtain A perforated modified natural graphite film with burrs on both sides; the thickness of the thermally conductive polyimide-based graphite film is 100 μm, the thickness of the perforated modified natural graphite film is 100 μm, and the thickness of the thermally conductive insulating layer is 5 μm, wherein the thermally conductive polyimide composite film, by weight, is prepared from raw materials including: 102.165 g of 4,4′-diaminodiphenyl ether, 54.07 g of p-phenylenediamine, 2170 g of dimethylacetamide, 227.2 g of pyromellitic anhydride, and 5 g of modified graphene oxide;

[0067] The method for preparing the thermally conductive polyimide composite film comprises the following steps:

[0068] S51. According to the mass fractions, 102.165 g of 4,4′-diaminodiphenyl ether and 54.07 g of p-phenylenediamine were added to the reactor at room temperature and in a nitrogen atmosphere, and then 2170 g of dimethylacetamide was added. After 4,4′-diaminodiphenyl ether and p-phenylenediamine were completely dissolved, the solution temperature was lowered to 10° C., 227.2 g of pyromellitic dianhydride was added to the solution, and the mixture was stirred for 24 h in an ice-water bath to obtain a yellow viscous polyamic acid solution.

[0069] S52, adding 8g of modified graphene oxide to the polyamic acid solution, mechanically stirring for 1h under a nitrogen atmosphere to mix the two evenly, vacuum degassing for 2h, and then coating on a clean and dry glass plate, and placing in a blast oven according to a gradient curing process of 80℃ / 1h+150℃ / 1h+250℃ / 1h+350℃ / 1h to dehydrate the polyamic acid to complete imidization, and after the film is cooled to room temperature, peel off the film in hot water, dry the water, and obtain a thermally conductive polyimide composite film;

[0070] The insulating thermal conductive coating is prepared from the following raw materials, calculated by weight: 22 g of insulating thermal conductive agent, 1.5 g of ethylene-ethyl acrylate copolymer, and 35 g of acetone.

[0071] The method for preparing the above-mentioned flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises the following steps:

[0072] S81, placing a perforated modified natural graphite film in the middle, covering the upper and lower surfaces with a thermally conductive polyimide composite film, performing the first calendering in a "sandwich structure", and undergoing carbonization, graphitization and a second calendering treatment to obtain a heat dissipation graphite sheet A; the process conditions for the carbonization are: carbonization at a temperature of 1400° C. for 1 h in a nitrogen atmosphere; the process conditions for the graphitization are: graphitization at a temperature of 2850° C. for 1 h in a nitrogen atmosphere; the first calendering and the second calendering treatments are both performed by using a shell-type fast press at a pressure of 150 MPa for 20 s;

[0073] S82, mixing the insulating thermal conductive agent, ethylene-ethyl acrylate copolymer and acetone uniformly according to the weight ratio to obtain an insulating thermal conductive coating;

[0074] S83, applying the insulating thermal conductive coating to one side of the heat dissipation graphite sheet A, heating and curing, the heating temperature is 105° C., the curing time is 60 seconds, and a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet is obtained.

[0075] Example 3

[0076] A flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, the flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises, from bottom to top, a thermally conductive polyimide-based graphite film, a perforated modified natural graphite film, a thermally conductive polyimide-based graphite film and a thermally conductive insulating layer, the thermally conductive insulating layer is formed by coating an insulating thermally conductive coating, the thermally conductive polyimide-based graphite film is prepared by graphitizing a thermally conductive polyimide composite film, and the preparation method of the perforated modified natural graphite film is to perform calendering and perforation treatment on the modified natural flake graphite to obtain A perforated modified natural graphite film with burrs on both sides; the thickness of the thermally conductive polyimide-based graphite film is 80 μm, the thickness of the perforated modified natural graphite film is 150 μm, and the thickness of the thermally conductive insulating layer is 8 μm, wherein the thermally conductive polyimide composite film, by weight, is prepared from raw materials including: 102.165 g of 4,4′-diaminodiphenyl ether, 54.07 g of p-phenylenediamine, 2170 g of dimethylacetamide, 227.2 g of pyromellitic anhydride, and 7 g of modified graphene oxide;

[0077] The method for preparing the thermally conductive polyimide composite film comprises the following steps:

[0078] S51. According to the mass fractions, 102.165 g of 4,4′-diaminodiphenyl ether and 54.07 g of p-phenylenediamine were added to the reactor at room temperature and in a nitrogen atmosphere, and then 2170 g of dimethylacetamide was added. After 4,4′-diaminodiphenyl ether and p-phenylenediamine were completely dissolved, the solution temperature was lowered to 10° C., 227.2 g of pyromellitic dianhydride was added to the solution, and the mixture was stirred for 24 h in an ice-water bath to obtain a yellow viscous polyamic acid solution.

[0079] S52, adding 7g of modified graphene oxide to the polyamic acid solution, mechanically stirring for 1h under a nitrogen atmosphere to mix the two evenly, vacuum degassing for 2h, and then coating on a clean and dry glass plate, and placing in a blast oven according to a gradient curing process of 80℃ / 1h+150℃ / 1h+250℃ / 1h+350℃ / 1h to dehydrate the polyamic acid to complete imidization, and after the film is cooled to room temperature, the film is peeled off in hot water, and the water is dried to obtain a thermally conductive polyimide composite film;

[0080] The insulating thermal conductive coating is prepared from the following raw materials, calculated by weight: 21 g of insulating thermal conductive agent, 1.3 g of ethylene-ethyl acrylate copolymer, and 32 g of acetone.

[0081] The method for preparing the above-mentioned flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises the following steps:

[0082] S81, placing a perforated modified natural graphite film in the middle, covering the upper and lower surfaces with a thermally conductive polyimide composite film, performing the first calendering in a "sandwich structure", and undergoing carbonization, graphitization and a second calendering treatment to obtain a heat dissipation graphite sheet A; the process conditions for the carbonization are: carbonization at a temperature of 1350°C for 1 hour in a nitrogen atmosphere; the process conditions for the graphitization are: graphitization at a temperature of 2870°C for 1 hour in a nitrogen atmosphere; the first calendering and the second calendering treatments are both performed by using a shell-type fast press at a pressure of 150MPa for 18s;

[0083] S82, mixing the insulating thermal conductive agent, ethylene-ethyl acrylate copolymer and acetone uniformly according to the weight ratio to obtain an insulating thermal conductive coating;

[0084] S83, applying the insulating thermal conductive coating on one side of the heat dissipation graphite sheet A, heating and curing, the heating temperature is 100° C., the curing time is 65 seconds, and a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet is obtained.

[0085] Comparative Example 1

[0086] The same as Example 3, except that an equal amount of graphene oxide is used instead of modified graphene oxide.

[0087] Comparative Example 2

[0088] The same as Example 3, except that an equal amount of natural flake graphite is used instead of modified natural flake graphite.

[0089] Comparative Example 3

[0090] The same as Example 3, except that an equal amount of mica with a particle size of 2 microns is used to replace the insulating thermal conductive agent.

[0091] Performance testing

[0092] The bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheets prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were sampled and subjected to the following tests. The test results are shown in Table 1.

[0093] Thermal conductivity: Tested according to national standard GB / T2588-2008, using NETZSCH HY 009 thermal conductivity tester, at 25°C;

[0094] Specific heat capacity: tested according to national standard ASTME 1269-11;

[0095] Heat flux: tested according to national standard GB / T2588-2008;

[0096] Resistance test: According to GB / 1410-2006; the volume surface resistivity tester LST-121 is used to detect the surface resistance. The surface resistance test measures the surface resistance of the thermal conductive insulation layer.

[0097] Table 1 Performance test

[0098]

[0099] Analyzing the data in Table 1, we can see that:

[0100] 1) The flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheets prepared in Examples 1 to 3 have high thermal conductivity, high heat flux and electrical safety, and are widely used in electronic equipment, automobiles, aerospace and other fields, especially in scenarios that require efficient heat dissipation and maintaining equipment flexibility, such as flexible display screens, wearable devices, etc.

[0101] 2) The performance comparison analysis of the flexible high thermal conductivity and super-tough composite heat dissipation graphite sheet prepared in combination with Example 3 and Comparative Example 1 shows that the active functional groups such as carboxyl, hydroxyl, and epoxy carried by the modified graphene oxide prepared by adding can establish molecular interactions between the layers of the thermally conductive polyimide-based graphite film. This enhanced interfacial interaction is conducive to improving the overall mechanical properties and thermal stability of the material, while improving the thermal conduction efficiency between the layers. By introducing modified graphene oxide, the heat transfer limitation in the vertical direction can be improved, thereby significantly improving the vertical thermal conductivity of the thermally conductive polyimide-based graphite film. This is because modified graphene oxide helps to form a more continuous and orderly heat conduction path, reduce thermal resistance, and improve the thermal conductivity of the material. The introduction of modified graphene oxide not only improves the thermal conductivity, but also increases the flexibility and bendability of the composite material. This is particularly important for preparing high thermal conductivity and high flexibility heat dissipation materials that can be applied to flexible display screens, wearable devices and other fields.

[0102] 3) The performance comparison analysis of the bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet prepared in Example 3 and Comparative Example 2 shows that the modified natural flake graphite is modified by the Fenton reaction, so that a large number of defects and oxygen-containing functional groups are formed on the surface of the natural flake graphite. 3+ The OH adsorbed on the carbon fiber surface and free in the surrounding - It is converted into iron oxyhydroxide, and finally a protruding iron oxyhydroxide structure is formed on the surface of natural flake graphite, which is reduced to iron by carbon during the graphitization process to form a three-dimensional network structure, which significantly improves the compatibility and bonding strength with the perforated modified natural graphite film and the thermal conductivity channel, thereby improving the heat dissipation effect.

[0103] 4) A comparative analysis of the performance of the flexible, highly thermally conductive, ultra-tough composite heat dissipation graphite sheets obtained in combination with Example 3 and Comparative Example 3 shows that the thermally conductive insulating layer formed by coating the insulating thermal conductive coating obtained by preparing the insulating thermal conductive agent using methylphenyl silicone oil and mica has good insulation and thermal conductivity, so that the composite heat dissipation graphite sheet made of the insulating thermal conductive layer can play a good role in heat dissipation and insulation, thereby reducing the possibility of leakage.

[0104] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A flexible high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, characterized in that: The bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises, from bottom to top, a thermally conductive polyimide-based graphite film, a perforated modified natural graphite film, a thermally conductive polyimide-based graphite film and a thermally conductive insulating layer, wherein the thermally conductive insulating layer is formed by coating an insulating thermally conductive coating, and the thermally conductive polyimide-based graphite film is prepared by graphitizing a thermally conductive polyimide composite film; the thickness of the thermally conductive polyimide-based graphite film is 50-100 μm, the thickness of the perforated modified natural graphite film is 100-200 μm, and the thickness of the thermally conductive insulating layer is 5-10 μm, wherein the thermally conductive polyimide composite film, in terms of mass fractions, is prepared from raw materials comprising: 102.165 parts of 4,4′-diaminodiphenyl ether, 54.07 parts of p-phenylenediamine, 2170 parts of dimethylacetamide, 227.2 parts of pyromellitic anhydride, and 5-8 parts of modified graphene oxide; The preparation method of the modified graphene oxide comprises the following steps: S21, taking 100 parts of graphene oxide by mass and drying them in a vacuum drying oven at 100° C. for 12 h; S22, according to the mass fractions, 95 parts of ethanol and 5 parts of deionized water were mixed, the pH was adjusted to 4 with acetic acid, and then 1.2 parts of 3-[3-carboxyallylamide]propyltriethoxysilane were added dropwise and ultrasonically stirred for 1-2 hours to obtain a mixed solution; S23, adding 20 parts of dried graphene oxide to the mixed solution, heating the mixture to 62°C, stirring at a rate of 200 rpm, reacting for 4-5 hours, filtering, washing with anhydrous ethanol 3 times, and vacuum drying at 100°C for 24 hours to obtain modified graphene oxide; The method for preparing the perforated modified natural graphite film comprises: performing calendering and perforation treatment on modified natural flake graphite to obtain a perforated modified natural graphite film having burrs on both sides; The modification method of the modified natural flake graphite is as follows: 30g of natural flake graphite is placed in a reactor filled with 3L of pure water for ultrasonic treatment for 1-2h, and sufficient defect sites are formed on the surface under the action of ultrasonic cavitation, and then 150g of ferrous sulfate is added and stirred evenly, and then the temperature is raised to 85°C, and then 5L of hydrogen peroxide with a mass concentration of 30% is dripped into the reactor, reacted for 24h and cooled to room temperature, and the natural flake graphite is washed with pure water for 3 times, and then the modified natural flake graphite is dried at 60°C for 4h to obtain modified natural flake graphite; The method for preparing the thermally conductive polyimide composite film comprises the following steps: S51. According to the mass fractions, 102.165 parts of 4,4′-diaminodiphenyl ether and 54.07 parts of p-phenylenediamine were added to the reactor at room temperature and in a nitrogen atmosphere, and then 2170 parts of dimethylacetamide were added. After 4,4′-diaminodiphenyl ether and p-phenylenediamine were completely dissolved, the solution temperature was lowered to 10° C., 227.2 parts of pyromellitic dianhydride were added to the solution, and the mixture was stirred for 24 hours in an ice-water bath to obtain a yellow viscous polyamic acid solution. S52, adding 5-8 parts of modified graphene oxide to the polyamic acid solution, mechanically stirring for 1 hour under a nitrogen atmosphere to make the two mixed evenly, vacuum degassing for 2 hours, and then coating on a clean and dry glass plate, and placing in a blast oven according to a gradient curing process of 80°C / 1h+150°C / 1h+250°C / 1h+350°C / 1h to dehydrate the polyamic acid to complete imidization, and after the film is cooled to room temperature, peel off the film in hot water, dry the water, and obtain a thermally conductive polyimide composite film; The insulating thermal conductive coating is prepared from the following raw materials, calculated by weight: 20-22 parts of insulating thermal conductive agent, 1-1.5 parts of ethylene-ethyl acrylate copolymer, and 30-35 parts of acetone; The preparation method of the insulating thermal conductive agent comprises the following steps: S71, weighing 1 kg of mica with a particle size of 2 microns and 50 kg of xylene, placing them in ultrasonic vibration for 8 minutes to obtain a mixture A; S72, weighing 36 kg of methylphenyldimethoxysilane and 1.2 kg of tetramethyldivinyldisiloxane, mixing them evenly, adding them together with mixture A into the reaction kettle, stirring evenly, and heating to 50° C. to obtain mixture B; S73, weigh 3kg of 1.6% sodium hydroxide solution, add it dropwise to mixture B, stir evenly, heat to 72°C, hydrolyze for 2h, heat to 80°C, distill at normal pressure, react for 5h, heat to 92°C, distill under reduced pressure for 1h to remove the solvent and small molecule products, add anhydrous ethanol for washing, dry, and obtain an insulating thermal conductor; The method for preparing the bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet comprises the following steps: S81, placing a perforated modified natural graphite film in the middle, covering the upper and lower surfaces with a thermally conductive polyimide composite film, performing a first calendering in a "sandwich structure", and undergoing carbonization, graphitization and a second calendering treatment to obtain a heat dissipation graphite sheet A; S82, mixing the insulating thermal conductive agent, ethylene-ethyl acrylate copolymer and acetone uniformly according to the weight ratio to obtain an insulating thermal conductive coating; S83, coating an insulating thermally conductive coating on one side of the heat dissipation graphite sheet A, heating and curing the sheet, and obtaining a bendable, highly thermally conductive, and ultra-tough composite heat dissipation graphite sheet.

2. According to claim 1, a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, characterized in that: In step S81, the carbonization process conditions are: carbonization at a temperature of 1300-1400°C for 1 hour in a nitrogen atmosphere; the graphitization process conditions are: graphitization at a temperature of 2850-2890°C for 1 hour in a nitrogen atmosphere; the first calendering and the second calendering treatments are both performed using a shell-type fast press at a pressure of 150MPa for 15-20s.

3. According to claim 1, a bendable high thermal conductivity and ultra-tough composite heat dissipation graphite sheet, characterized in that: In step S83, the heating temperature is 90-105°C, and the curing time is 60-70s.

Citation Information

Patent Citations

  • High-thermal-conductivity composite graphite cooling fin and preparation method thereof

    CN113587061A

  • High-thermal-conductivity insulating cooling fin for new energy battery and preparation method of high-thermal-conductivity insulating cooling fin

    CN114316328A

  • Method for preparing high-thermal-conductivity polyimide graphite film through chemical imidization of doped graphene

    CN116375016A